Tembikar Tera-Tali di Situs Buttu Batu Enrekang: Suatu Rekonstruksi Pengaruh Austroasiatik - Putri, Andini Dwi; Hasanuddin; Muda, Khadijah Thahir (Badan Riset dan Inovasi Nasional, 2022)
Past civilizations showed specific patterns of development that reflected their mastery of technology and behavior. Cultural developments took the form of technological developments such as pottery, pickaxes, axes, jewelry, and ike stones. The Buttu Batu site, located in Enrekang (South Sulawesi), is evidence of the development of human life with the discovery of traces of past human activity in the form of pottery fragments, stone artifacts, bones, jewelry, and ike stones. One form of decorative motif on pottery fragments found at this site is a pottery fragment decorated with cord-marked. As is known, cord-marked pottery is evidence of a western route migration (migration of Austroasiatic speakers). The methods used to achieve the research objectives were field data collection, data processing in shape analysis, and stylistic analysis, especially for cord-marked pottery. The discovery of cord-marked pottery fragments in Enrekang Regency shows that the western migration route (Austroasiatic) probably migrated to the eastern part of Indonesia, especially the South Sulawesi region, and this requires further investigation.